2019
DOI: 10.1523/jneurosci.0749-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Inhibition during Developmental Hearing Loss Rescues Auditory Learning and Perception

Abstract: Transient periods of childhood hearing loss can induce deficits in aural communication that persist long after auditory thresholds have returned to normal, reflecting long-lasting impairments to the auditory CNS. Here, we asked whether these behavioral deficits could be reversed by treating one of the central impairments: reduction of inhibitory strength. Male and female gerbils received bilateral earplugs to induce a mild, reversible hearing loss during the critical period of auditory cortex development. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 148 publications
(191 reference statements)
5
35
0
Order By: Relevance
“…However, lasting changes in the dynamics of inhibitory synapses after sensory deprivation may be circuit dependent. In the A1, developmental hearing loss can induce enduring disinhibition and behavioral deficits that can be improved by restoring the inhibitory tone (Mowery et al, 2019), whereas visual deprivation triggers circuit-specific changes in the V1 that can result in increased inhibitory tone in local cortical circuits (Maffei et al, 2006;Kannan et al, 2016;Miska et al, 2018). While it is still unclear if these differences stem from distinct mechanisms of homeostasis in response to sensory manipulations, studies agree that the fast dynamics of inhibitory neurotransmission may be the key to sensory adaptations during the critical periods (Gainey and Feldman, 2017).…”
Section: Plasticity In the Developing Cortexmentioning
confidence: 99%
“…However, lasting changes in the dynamics of inhibitory synapses after sensory deprivation may be circuit dependent. In the A1, developmental hearing loss can induce enduring disinhibition and behavioral deficits that can be improved by restoring the inhibitory tone (Mowery et al, 2019), whereas visual deprivation triggers circuit-specific changes in the V1 that can result in increased inhibitory tone in local cortical circuits (Maffei et al, 2006;Kannan et al, 2016;Miska et al, 2018). While it is still unclear if these differences stem from distinct mechanisms of homeostasis in response to sensory manipulations, studies agree that the fast dynamics of inhibitory neurotransmission may be the key to sensory adaptations during the critical periods (Gainey and Feldman, 2017).…”
Section: Plasticity In the Developing Cortexmentioning
confidence: 99%
“…Up or downregulation of GABAA-α1 containing receptors has previously been shown to govern mature forms of inhibitory synaptic transmission (Fritschy et al, 1994;Heinen et al, 2004;Bosman et al, 2005). Hence, restoration of GABAergic inhibition in cases of behavioral deficits could be a valuable target to investigate for potential therapy approaches (Verret et al, 2012;Schmid et al, 2016;Dargaei et al, 2018;Mowery et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, cochlear ablation prior to hearing onset (Sanes et al, 1992) or deafness in the deafness (dn/dn) mutant mouse (Oleskevich and Walmsley, 2002) led to larger EPSP amplitudes and lower inhibitory synaptic strength. This phenomenon was observed in the cochlear nucleus (Oleskevich and Walmsley, 2002), in the lateral lemniscus, and in IC neurons (Sanes et al, 1992), as well as in thalamocortical and intracortical primary auditory cortex neurons (Kotak et al, 2005(Kotak et al, , 2013Mowery et al, 2019). It was suggested that the larger EPSP amplitudes in congenital deafness may result from an increase in AMPA-and non-NMDA receptors and a decrease in inhibitory postsynaptic potential conductance.…”
Section: Failed Maturation Of Fast Auditory Processing Following Congenital Deafnessmentioning
confidence: 96%
“…Imbalances in excitation and inhibition are observed in acquired deafness, which can be caused by cochlear damage, middle-ear ossicle removal, acoustic trauma, or drug-induced deafness ( Kotak et al, 2013 ; Mowery et al, 2019 ). In previous studies, it was shown that acquired deafness in mature animals led to hyperexcitability that coincided with a decrease in GABA and glutamic acid decarboxylase (GAD65) ( Bledsoe et al, 1995 ; Abbott et al, 1999 ).…”
Section: Altered Excitation and Inhibition In Acute Acoustic Trauma Deafness And Tinnitus: Lost Fast Auditory Processingmentioning
confidence: 99%